Estratégias discursivas por meio de orações adverbiais introduzidas por como e se no português - Stassi-Sé, Joceli Catarina; Pezatti, Erotilde Goreti [UNESP] (FapUNIFESP (SciELO), 2017)
In the view of the theoretical model of Functional Discourse Grammar (Hengeveld & Mackenzie 2008), this study is about clauses introduced by como(as) and se(if) that present the form of an adverbial subordinated clause although they do not formally depend from a main clause. The universe of investigation is the Corpus of Spoken Portuguese Project- Social and Geographic Varieties. The investigation shows that these constructions are used in the monitoring of the interaction, to reactivate, in the memory of the interlocutor, given information from the discourse (constructions with como(as) and to save the face of the Speaker, as a strategy of face preservation (constructions with se(if).
Discursive strategies in adverbial clauses introduced by como as and se if in portuguese
Keywords: Adverbial clause; Discourse strategies; Functionalism; Subordination